First experiments on ICRF discharge generation by a W7-X-like antenna in the Uragan-2M stellarator. (October 2020) - Moiseenko, V. E.; Kovtun, Yu. V.; Wauters, T.; Goriaev, A.; Lyssoivan, A. I.; Lozin, A. V.; Pavlichenko, R. O.; Shapoval, A. N.; Maznichenko, S. M.; Korovin, V. B.; Kramskoy, E. D.; Kozulya, M. M.; et al.
Abstract : In support of the ICRF experiments planned on the Wendelstein 7-X (W7-X) stellarator, i.e. fast ion generation, wall conditioning, target plasma production and heating, a first experimental study on plasma production has been made in the Uragan-2M (U-2M) stellarator using W7-X-like two-strap antenna. In all the experiments, antenna monopole phasing was used. The W7-X-like antenna operation with launched radiofrequency power of 100 kW have been performed in helium ( p = (4–14) × 10 −2 Pa) with the vacuum vessel walls pre-loaded with hydrogen. Production of plasma with a density higher than 10 12 cm −3 was observed near the first harmonic of the hydrogen cyclotron frequency. Operation at first hydrogen harmonic is feasible in W7-X future ICRF experiments.